EFEKTIVITAS MEDIA PUBLIKASI ONLINE BENTARA BUDAYA BALI (AGENDA BERKALA: SINEMA BENTARA PERIODE JANUARI-MARET 2017) - Siswan Dewi, Ni Made; Purnawan, Ni Luh Ramaswati; Pradipta, Ade Devia (E-Jurnal Medium, 2018)
ABSTRACT Only few cultural public spaces that can periodically and continuously organize cultural arts activities, while maintaining and managing communications with the public. As a non-profit public space, Bentara Budaya Bali has a public relation that manages publications through various online media. Utilization of online publication media is also an effort of the mission of ’transfer of knowledge’ or the extension of awareness through the knowledge that arranged in such a way in editorial publication. The agenda of Bentara Budaya Bali which utilizes this kind of online publication media is Sinema Bentara.The purpose of this research is to know how the effectiveness of Bentara Budaya Bali online publication media in informing the agenda of Sinema Bentara, and to know which online publication media is the most effective. This type of research is quantitative with a descriptive statistical approach. The technique of collecting data of this research is questionnaire to the visitors of Sinema Bentara from January until March 2017. Keywords: Bentara Budaya Bali, Online Media, Public Relations, Publication, Sinema Bentara